Identification of the inhibition mechanism of carbonic anhydrase II by fructooligosaccharides - Mu, Yue; Meng, Qingyang; Fan, Xinyi; Xi, Shuyun; Xiong, Zhongli; Wang, Yihua; Huang, Yanling; Liu, Zhen (Frontiers in Molecular Biosciences, 2024)
Polygonatum sibiricum (P. sibiricum), recognized as a precious nourishing Chinese traditional medicine, exhibits the pharmacological effect of anti-aging. In this work, we proposed a novel mechanism underlying this effect related to the less studied bioactive compounds fructooligosaccharides in P. sibiricum (PFOS) to identify the inhibition effect of the small glycosyl molecules on the age-related zinc metalloprotease carbonic anhydrase II (CA II). Molecular docking and molecular dynamics simulation were used to investigate the structural and energetic properties of the complex systems consisting of the CA II enzyme and two possible structures of PFOS molecules (PFOS-A and PFOS-B). The binding affinity of PFOS-A (-7.27 ± 1.02 kcal/mol) and PFOS-B (-8.09 ± 1.75 kcal/mol) shows the spontaneity of the binding process and the stability of the combination in the solvent. Based on the residue energy decomposition and nonbonded interactions analysis, the C-, D-and G-sheet fragments of the CA II were found to be crucial in binding process. Van der Waals interactions form on the hydrophobic surface of CAII mainly with 131PHE and 135VAL, while hydrogen bonds form on the hydrophilic surface mainly with 67ASN and 92GLN. The binding of PFOS results in the blocking of the zinc ions pocket and then inhibiting its catalytic activity, the stability of which has been further demonstrated by free energy landscape. These findings provide evidence of the effective inhibition of PFOS to CA II enzyme, which leads to a novel direction for exploring the mechanism of traditional Chinese medicine focused on small molecule fructooligosaccharides.